1999
DOI: 10.1159/000013835
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Components of the Human Middle Ear and Simulation of Their Dynamic Behaviour

Abstract: In order to get a better insight into the function of the human middle ear it is necessary to simulate its dynamic behaviour by means of the finite-element method. Three-dimensional measurements of the surfaces of the tympanic membrane and of the auditory ossicles malleus, incus and stapes are carried out and geometrical models are created. On the basis of these data, finite-element models are constructed and the dynamic behaviour of the combinations tympanic membrane with malleus in its elastic suspensions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…Many mathematical middle-ear models have used simply supported, fully clamped, or a combination for the boundary conditions of the TM (Funnell 1975;Funnell and Laszlo 1978;Funnell et al 1987Funnell et al , 1992Funnell and Decraemer 1996;Rabbitt & Holmes 1986;Ladak & Funnell 1996;Beer et al 1996Beer et al , 1999Fay et al 2006;Elkhouri et al 2006;Eiber et al (2000); Ladak et al 2006;Qi et al 2008). Changing a model from simply supported to fully clamped boundary conditions may cause differences in response that, depending on the characteristics of the model and the magnitude of the applied load, may be more or less important.…”
Section: Boundary Conditions In Mathematical Modelsmentioning
confidence: 99%
“…Many mathematical middle-ear models have used simply supported, fully clamped, or a combination for the boundary conditions of the TM (Funnell 1975;Funnell and Laszlo 1978;Funnell et al 1987Funnell et al , 1992Funnell and Decraemer 1996;Rabbitt & Holmes 1986;Ladak & Funnell 1996;Beer et al 1996Beer et al , 1999Fay et al 2006;Elkhouri et al 2006;Eiber et al (2000); Ladak et al 2006;Qi et al 2008). Changing a model from simply supported to fully clamped boundary conditions may cause differences in response that, depending on the characteristics of the model and the magnitude of the applied load, may be more or less important.…”
Section: Boundary Conditions In Mathematical Modelsmentioning
confidence: 99%
“…The anatomical features include the morphometry of the middle-ear bones as well as the morphometry of the soft tissues. Inertial properties of the middle-ear bones for human (Kirikae 1960;Beer et al 1999;Weistenhö fer and Hudde 1999;Puria et al 2007a;Sim et al 2007) and for cat, guinea pig, and chinchilla (Puria et al 2007a) have been reported previously. However, detailed morphometry of the soft tissues such as their dimensions and relative positions mostly remains unknown.…”
Section: Introductionmentioning
confidence: 71%
“…A number of groups have since used the finiteelement method to study the mechanics of the eardrum and ossicles in humans (Wada et al 1992;Beer et al 1999;Bornitz et al 1999;Prendergast et al 1999;Koike et al 2002;Sun et al 2002) and in cats (Funnell and Laszlo 1978;Funnell et al 1987;Ladak and Funnell 1996;Funnell et al 2005). The geometries have generally been oversimplified and material properties have often been based on curve fitting.…”
Section: Introductionmentioning
confidence: 99%